Kinetics and mechanism of hydrolysis of N-Arylphthalimides - Ariffin, Azhar; Khan, M.N.; Sim, Y.L.; Ahmad, W.H.W.; Cheong, M.Y. (2009)
The values of pseudo-first-order rate constants, k(obs), for hydrolysis of N-(2 '-methoxyphenyl) phthalimide (1) increase linearly with increase in [HCl] over the range 5 x 10(-3) -1.0M at 8.0 x 10(-5) M 1, 0.5 M mu (by NaCl) and in the temperature range 30 40 degrees C. The rate of acidic hydrolysis of N-(4'-methoxyphenyl)phthalimide (2) reveals behaviour similar to that found for 1, N-(2'-hydroxyphenyl)phthalimide (3) and N-(4'-aminophenyl)phthalimide (4). The values of k(obs) at 35 degrees C and varying [HCl] give the respective rate constants for the [HCl]-independent (k(0)) and the [HCl]-dependent (k(H)) hydrolysis of 1 (at [1(0)] = 8.0 x 10(-5) M, mu = 0.5M) as 6.74 x 10(-7) s(-1) and 5.47 x 10(-6) M(-1) s(-1), 2 (at [2(0)] = 3.0 x 10(-5) M, mu = 0.5 M) as 12.2 x 10(-7) s(-1) and 4.61 x 10(-6) M(-1) s(-1) and 4H(+) (at [4(0)] = 2.0 x 10(-4) M, mu = 1.0 M) as 5.83 x 10(-7) s(-1) and 15.2 x 10(-6) M(-1) s(-1). The values of k(w)/k(0)(min) are of the order of 10(2) for 1, 2 and 4 where k(0)(min) represents the sum of the contributions of H(+)- and HO(-)-catalysed hydrolysis towards k(0) (first-order rate constant for pH-independent hydrolysis of imide) and k(w) is the pseudo-first-order rate constant for the uncatalysed reaction of H(2)O with imide.